2020
DOI: 10.1002/pri.1887
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural adaptation of Life Satisfaction Checklist‐11 among persons with stroke in China: A reliability and validity study

Abstract: Objective The aim of the present study was to develop a cross‐cultural adaptation and to evaluate the validity and reliability of a Chinese version of the LiSat‐11 test. Methods LiSat‐11 was translated into Chinese according to standardized procedures. A cross‐sectional descriptive study was conducted to examine its reliability and validity, in accordance to COnsensus‐based Standards for the election of health Measurements Instruments guidelines, among persons with stroke approximately 3 years after their disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Appraisals include perceptions and interpretations of events with personal meaning, relevant for one's self and future wellbeing (Ashar et al, 2017). Several lines of research have proposed neurocognitive and biological models for the relationship between negative appraisal of events and emotion (Folkman et al, 1986;Lazarus, 1991;Scherer et al, 2001), and a cognitive model that links negative appraisal of life events to depression has been put forward (Sander et al, 2018;Wang et al, 2021). In this context, our results showed that negative appraisals of experience and body interception are associated with worse MH.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Appraisals include perceptions and interpretations of events with personal meaning, relevant for one's self and future wellbeing (Ashar et al, 2017). Several lines of research have proposed neurocognitive and biological models for the relationship between negative appraisal of events and emotion (Folkman et al, 1986;Lazarus, 1991;Scherer et al, 2001), and a cognitive model that links negative appraisal of life events to depression has been put forward (Sander et al, 2018;Wang et al, 2021). In this context, our results showed that negative appraisals of experience and body interception are associated with worse MH.…”
Section: Discussionmentioning
confidence: 64%
“…Positive appraisals seem to contribute to homeostasis, representing a signal indicating to the body to return to equilibrium (Burgdorf & Panksepp, 2006). Positive appraisal, a domain covering happiness and life satisfaction, is associated with success across life domains, including social, occupational, physical and psychological health (Wang et al, 2021). Positive appraisals seem to build the physical, intellectual and social capacity to promote long-term survival (Alexander et al, 2021).…”
Section: Discussionmentioning
confidence: 99%